PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN MODAL TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR AGRICULTURE DI BURSA EFEK INDONESIA PERIODE 2018-2020 - NAOMI THERESIA IRMAWAN; LENITA WATY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to determine the effect of cash turnover, receivables turnover, inventory turnover, and working capital turnover on the profitability of agriculture sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The independent variables in this study are cash turnover, accounts receivable turnover, and working capital inventory turnover. And the dependent variable in this study is profitability. The population in this study are agriculture sector companies listed on the Indonesia Stock Exchange. The sampling technique used in this study used a purpose sampling technique. According to the criteria that have been set in the sampling, there are 8 companies that fit the criteria. The type of data used is secondary data taken by the documentation method by accessing the www.idx.co.id site. As well as the sites of each company. The analysis technique used is multiple linear regression analysis technique. The results showed that: (1) There is a positive influence between cash turnover on company profitability. (2) There is no influence between receivables turnover on company profitability. (3) There is a positive influence between inventory turnover on company profitability. (4) There is a negative influence between working capital turnover on company profitability.